A quick bite and instant gratification: A simulated Yelp experiment on consumer review information foraging behavior. Issue 1 (January 2021) - Nakayama, Makoto; Wan, Yun
Highlights: Consumers overestimate their expected search effort before using a review site. Compared to consumers who had used Yelp before, those who had never used Yelp expect their browsing duration and review counts to be 42% and 93% higher, respectively. Before making a decision, most consumers spend only five minutes or less, read five or fewer reviews, and browse seven to eight pages. What information "patches" consumers see within those limited ranges may significantly influence the restaurant choices . Abstract: In the post-industrial information-based economy, classical information economics models are often used to explain consumer choices and decision-making behaviors. However, many heuristic consumer behaviors are better explained by behavioral ecology models, such as information foraging. In this study, we examined how consumers explore task-oriented review information in an online environment where they may or may not have prior visiting experience. Our findings indicate that consumers overestimate their expected search effort before using a review site. Compared with consumers who had used Yelp before, those who had never used the site expect their browsing duration and review counts to be 42% and 93% higher, respectively. In addition, before making a decision, most consumers spend only five minutes or less, read five or fewer reviews, and browse seven to eight pages. This finding indicates the review information consumers choose to use within those limited-time ranges may significantly influence the restaurant choices of those foraging consumers.